PEMEROLEHAN BAHASA ANAK PADA USIA DINI DALAM ASPEK FONOLOGI - widia agustina; Ika Mustika; Riana Lestari (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Language is an important thing to people for making communicate. Language acquisition is an ongoing process in a child’s brain when they got their first language or the mother tongue. Children  acquiring language start from they learn to speak. The aim of this study was to find out the acquisition of children’s language at the age of three in terms of phonological aspects which include, vowels, consonants, and diphthongs. In addition, the study is also intended to assist parents in supervising the development of their language. The method used in this research is descriptive qualitative method. With this method the research results are described in accordance with the objectives, so that the data obtained is easy to inform. The results obtained in this study were 23 pronunciation of vowels, 28 pronunciation of consonants, and 7 pronunciation of diphthong letters. Consonants are more dominant in letters. At the least dftong pronunciation.